Tradition-based Modern Creations of a Cultural Community Some Thoughts on the Copyright Status of Internet Folklore - Pogácsás Anett (SANTANDER ART AND CULTURE LAW REVIEW, 2024)
Folklore is not only an essential part of our cultural heritage, it is also an extremely important means of communication and expression. Although many theories try to capture the concept of “modern folklore” that is emerging at the present, only its main characteristics can be considered. When it comes to understanding internet folklore the ground is even more fragile, especially if we wish to examine and assess it not exclusively through a folkloristic lens, but also from a copyright perspective. There is a tendency to identify its natural presence based on a kind of simplicity, and to project that simplicity not only with respect to its use, but also with respect to the legal regulation that applies to it. The present study aims to show how internet folkore has to fit into an incredibly complex set of copyright rules, and how not only its creation but also its use for various purposes and in several different ways raises different copyright issues from one jurisdiction to another. As UNESCO clearly points out, intangible cultural heritage is community-based, but raising awareness and emphasizing its importance is a universal task. In this context, a cultural community needs to find a place for tradition-based modern creations such as internet folklore, without disregarding their copyright status and future.